2022
DOI: 10.14740/wjon1532
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal Small Bowel Metastasis From Primary Lung Cancer

Abstract: Lung cancer is the leading cause of cancer-related death worldwide, with frequent metastases to the brain, liver, adrenal glands, and bone. The incidence of intraluminal small bowel metastases of the lung is extremely rare and poorly documented within the literature. Few case studies have been published since the late 1980s and early 1990s. However, little is known about this rare form of metastasis. Small bowel metastatic disease has atypical symptoms that mimic a variety of other diseases; as a result, signs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Notably, 85% of these patients also had metastases at other sites, and six of them passed away within eight months following bowel resection [ 5 ]. Kosciuszek ND et al reported 11 cases of NSCLC with small bowel metastasis over the past five years [ 6 ]. The majority (seven patients) had lung adenocarcinoma as their primary lung cancer, and there were no reported cases of squamous cell carcinoma with small bowel metastasis during this period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, 85% of these patients also had metastases at other sites, and six of them passed away within eight months following bowel resection [ 5 ]. Kosciuszek ND et al reported 11 cases of NSCLC with small bowel metastasis over the past five years [ 6 ]. The majority (seven patients) had lung adenocarcinoma as their primary lung cancer, and there were no reported cases of squamous cell carcinoma with small bowel metastasis during this period.…”
Section: Discussionmentioning
confidence: 99%
“…It has been inadequately documented in medical literature. Only a handful of cases of lung cancer with small bowel metastasis have been reported, primarily between 1980 and 1999 [6][7][8][9]. Consequently, this uncommon form of metastasis remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jejunum (50.9%) is the most frequently involved site for small bowel metastasis from lung cancer, followed by ileum (33.3%) and rarely duodenum (15.8%) [ 12 ]. Our patient was diagnosed with adenocarcinoma lung, histologically, squamous cell carcinoma lung is more commonly seen as GI metastasis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%